Peranan Guru Agama Hindu Dalam Menanamkan Nilai Karakter Kepada Siswa Di SMP Negeri 1 Petang Kecamatan Petang, Kabupaten Badung - Kadek Suriasih (Jayapangus Press, 2018)
Education is something that cannot be separated from life, because from birth humans have received education, namely from the central education tri. Formal education will be obtained from the family environment and non-formal education from the community, while formal education will be obtained from the school environment. In school teachers play an important role, especially Hinduism teachers in order to educate the nation's life and shape the behavior of students to become students with good character. In order to be a student who has faith, devotion, knowledge, discipline, creative, independent and responsible. But in reality at present due to the development of increasingly modern times and technology, there is a lot of shifting moral values ​​in students decreasing manners and ethics of students towards parents at home, teachers and society, skipping school, when the learning process takes place students playing and not paying attention to the teacher who is teaching in class, likes to violate discipline and order, lying, rarely doing assignments or homework, lazy to pray at school and not even often we see students often speeding on the road, drunk liquor , smoking, sexual harassment, drug involvement, vandalism and theft, brawls between students and other irregularities that can damage students' mentality. To overcome this, Hinduism teacher schools in particular must increase their role, besides being educators who provide knowledge to students but must be able to shape student behavior, by instilling character values ​​such as religious, tolerance, honesty, discipline, responsibility and other character values ​​adapted to the teachings of Hinduism about ethics and morality.